PERLINDUNGAN HUKUM BAGI NASABAH PERBANKAN TERHADAP KEJAHATAN KARTU KREDIT - Sri Wulandari (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
Banking in facing the pace of technology in financial transactions in the use of credit cards as a means of payment runs safely. Protection of bank customers against misuse of credit cards so that customers are in a disadvantaged position. This study uses secondary data / literature as primary data supported by primary data, descriptive qualitative data presentation. Credit card crime has not been formulated normatively in Indonesia's positive law. The National Legal Development Agency (BPHN) tries to identify forms of cyberspace (credit card) activities with the Criminal Code, Banking Law, ITE Law and Consumer Protection Law. The policy regarding the regulation of credit card crimes is unclear, Article 263 and Article 378 of the Criminal Code are not relevant to be used to deal with criminal acts of credit card misuse, because there are some weaknesses that credit cards cannot be interpreted as letters. Therefore, legal protection for credit card customers can be surprised if there is participation from various parties regarding their rights and obligations, while the bank must be more open with credit card customers. Efforts to tackle credit card crime are carried out by means of a penal and non-penal policy that is to ensnare carders (credit card criminals) with the Criminal Code Articles by maximizing criminal threats and preventive measures by improving the credit card operational standard system as a form of security .